Body image mediates an association between personality and mental health. (4th September 2017) - Allen, Mark S.; Celestino, Serena
Abstract: Personality and body image have been identified as important correlates of mental and physical health. This study sought to explore whether body image mediates the association between the major dimensions of trait personality and self‐reported mental and physical health. In total, 451 Australian adults (121 men, 331 women; M age  = 21.88 ± 7.65 years) completed questionnaires at a single time‐point. After controlling for some demographic and anthropometric factors (e.g., body mass index), neuroticism was associated with all components of body image and mental and physical health. Extraversion, openness, and conscientiousness were associated with mental health and some components of body image. Multiple mediator models identified body image discrepancy and appearance evaluation as mediating the association between personality (neuroticism, extraversion, and conscientiousness) and mental health. No significant mediation effects were observed for physical health, and mediation effects were not moderated by participant gender. These findings provide evidence that personality relates to self‐reported mental health, in part, through the variance shared with body image.